Idiopathic renal replacement lipomatosis: A diagnostic and therapeutic challenge - Bhat, Gajanan (Turk J Surg, 2018)
Renal replacement lipomatosis is a rare benign renal disorder where the renal parenchyma is replaced by mature fatty tissue. It poses a diagnostic challenge to the clinicians due to an unusual presentation and clinical features. The disease usually presents in middle age with vague pain in the affected flank and variable urological symptoms. Although the condition is preceded by calculus disease or chronic inflammation, as an extremely rare occurrence, it can occur without any pre-existing condition, as in our case. Increasing awareness among the surgeons about the existence of such a condition will help the surgical fraternity to diagnose and manage such cases properly.